Loofah / lithium disilicate glass composite hydrogel, and preparation method and application thereof

CN122874651APending Publication Date: 2026-10-09NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611303162.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0004]综上所述,现有丝瓜络基骨修复材料仍存在以下技术缺陷:(1)脱木质素造成的纤维表面微观损伤难以修复,力学性能恢复不充分;(2)功能离子(如Zn2+)释放不可控,存在突释毒性与长效活性不足的矛盾;(3)缺乏抗氧化、抗炎等免疫调控功能,难以应对感染性骨缺损的复杂微环境;(4)难以实现力学支撑、可控离子释放、抗菌、抗炎、成骨等多功能的协同集成

Benefits of technology

1、本发明首次采用单宁酸对脱木质素丝瓜络进行表面修复,并与离子交换二硅酸锂玻璃粉末及聚乙烯醇复合,构建了纤维骨架-无机颗粒-聚合物基体三相协同增强体系,单宁酸分子中丰富的多酚羟基一方面有效填充并修复了脱木质素产生的纤维表面微观损伤,另一方面作为分子桥增强了纤维骨架与聚乙烯醇基体之间的界面结合,从而使复合水凝胶的力学性能显著优于未经单宁酸修饰或未添加生物活性玻璃的对比材料,其抗压强度达到与人体松质骨适配的水平,能够为骨缺损修复提供充足的力学支撑。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122874651A_ABST
    Figure CN122874651A_ABST
Patent Text Reader

Abstract

The application discloses a luffa / silicon dioxide glass composite hydrogel, which comprises a luffa fiber skeleton which is surface repaired by delignification and tannic acid, and a composite hydrogel matrix which fills and coats the fiber skeleton, and discloses a preparation method of the composite hydrogel: 1, after delignification, surface repair by a tannic acid solution; 2, preparation of lithium disilicate glass; 3, ion exchange of the lithium disilicate glass; 4, preparation of a precursor solution by a polyvinyl alcohol solution and ion-exchanged lithium disilicate glass powder; 5, penetration and freeze-thaw cycle crosslinking to obtain the luffa / silicon dioxide glass composite hydrogel. 2+ / Zn 2+ The composite hydrogel has controllable Cu 2+ / Zn 2+ dual ion release capacity, good mechanical properties, excellent biocompatibility, and exhibits antioxidant, anti-inflammatory, antibacterial and in-vitro osteogenic induction activities, and can be applied to preparation of bone tissue engineering scaffold materials, wound dressings or tissue repair materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomedical materials technology, specifically relating to a loofah / lithium disilicate glass composite hydrogel, its preparation method, and its application. Background Technology

[0002] Repairing infected bone defects is a major challenge in clinical medicine and tissue engineering. Ideal bone repair materials not only need to have good biocompatibility and mechanical properties that match the host bone, but also should have multiple biological functions such as antibacterial, anti-inflammatory, antioxidant, and osteogenic induction to address the inhibition of bone regeneration by the complex infection microenvironment.

[0003] Luffa sponge (LS), as a natural porous cellulose material, possesses a unique three-dimensional interconnected fiber skeleton and hierarchical pore structure, showing broad application prospects in the field of tissue engineering. In existing technologies, researchers have incorporated luffa sponge into hydrogel systems to enhance mechanical properties. For example, invention patent CN118599141A discloses a delignified luffa sponge-based hydrogel, which, after lignin removal using sodium chlorite, utilizes Fe... 3+ A tannic acid-based autocatalytic system was used to initiate acrylamide polymerization to prepare a loofah / polyacrylamide composite hydrogel. However, this system utilizes chemical polymerization and cross-linking of acrylamide, leaving residual monomers that pose a potential cytotoxic risk and lacking antibacterial, osteogenic, and other bioactive functions. Furthermore, another study (ACS Appl. Polym. Mater. 2026, 8, 5883-5896) used Zn... 2+ Coordination-modified delignified loofah sponge, combined with hydroxyapatite (HA) / polyvinyl alcohol (PVA) hydrogel, yielded certain mechanical strengthening and antibacterial osteogenic properties. However, the Zn content in this system... 2+ It mainly adheres to the fiber surface in a coordination manner, making it difficult to effectively repair submicron-level corrosion pores caused by delignification, resulting in limited mechanical recovery; at the same time, HA has limited effect on Zn 2+ Its controlled release capacity is insufficient, which can easily lead to cytotoxicity caused by ion burst release. Furthermore, it lacks antioxidant and anti-inflammatory functions and cannot meet the needs of the microenvironment of infectious bone defects for immune regulation.

[0004] In summary, existing loofah-based bone repair materials still have the following technical defects: (1) Microscopic damage to the fiber surface caused by delignification is difficult to repair, and mechanical properties are not fully restored; (2) Functional ions (such as Zn) 2+ (3) The release is uncontrollable, and there is a contradiction between burst toxicity and insufficient long-term activity; (4) It lacks immune regulation functions such as anti-oxidation and anti-inflammation, and it is difficult to cope with the complex microenvironment of infectious bone defects; (5) It is difficult to achieve the synergistic integration of multiple functions such as mechanical support, controllable ion release, antibacterial, anti-inflammatory and osteogenic.

[0005] Therefore, developing a multifunctional composite hydrogel based on loofah sponge that can solve the above problems simultaneously has important clinical significance. Summary of the Invention

[0006] The technical problem to be solved by this invention is to address the shortcomings of the prior art by providing a method for preparing a loofah / lithium disilicate glass composite hydrogel. This method involves surface repair of delignified loofah with tannic acid solution, followed by composite formation with lithium disilicate glass undergoing ion exchange in a mixed molten salt, resulting in a loofah / lithium disilicate glass composite hydrogel. This composite hydrogel possesses mechanical properties compatible with cancellous bone and controllable Cu content. 2+ / Zn 2+ With dual ion release capability, excellent antioxidant activity, long-lasting antibacterial properties, and good in vitro osteogenic induction ability, it overcomes the shortcomings of existing loofah-based bone repair materials, such as insufficient repair of microscopic damage to the fibrous skeleton, uncontrollable release of functional ions, lack of antioxidant and anti-inflammatory functions, and difficulty in synergistic integration of multiple properties.

[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a loofah / lithium disilicate glass composite hydrogel, characterized in that the composite hydrogel includes a loofah fiber skeleton that has been surface-repaired by delignification and tannic acid, and a composite hydrogel matrix that fills and coats the loofah fiber skeleton; the composite hydrogel matrix is ​​composed of polyvinyl alcohol and ion-exchange lithium disilicate glass powder.

[0008] In addition, the present invention also provides a method for preparing a loofah sponge / lithium disilicate glass composite hydrogel, characterized in that the method includes the following steps: Step 1: The loofah sponge is subjected to delignification treatment to obtain delignified loofah sponge. Then, the delignified loofah sponge is soaked in tannic acid solution for surface repair to obtain tannic acid surface-repaired loofah sponge fiber skeleton. Step 2: Prepare lithium disilicate glass using lithium carbonate and silicon dioxide as raw materials; Step 3: Place the lithium disilicate glass prepared in Step 2 in a container containing Zn. 2+ and Cu + The mixture of molten salts is subjected to ion exchange treatment, followed by crushing and grinding to obtain ion-exchanged lithium disilicate glass powder; Step 4: Mix polyvinyl alcohol with water and heat to dissolve, forming a polyvinyl alcohol solution. Then add the ion-exchange lithium disilicate glass powder obtained in Step 3 and stir evenly to obtain a precursor solution. Step 5: Immerse the tannic acid-repaired loofah fiber skeleton obtained in Step 1 into the precursor solution obtained in Step 4, perform infiltration treatment under negative pressure, and then perform at least one freeze-thaw cycle crosslinking to obtain a loofah / lithium disilicate glass composite hydrogel.

[0009] This invention removes lignin and hemicellulose from loofah sponges through delignification treatment, fully exposing the active hydroxyl groups on the cellulose skeleton surface. Surface repair is then performed using a tannic acid solution, repairing the microscopic damage to the fiber surface caused by delignification and enhancing the interfacial bonding between the loofah sponge and the subsequent polyvinyl alcohol matrix. Lithium disilicate glass is prepared using lithium carbonate and silica, and Zn is introduced through ion exchange in a molten salt. 2+ and Cu + This yields ion-exchange lithium disilicate glass powder, which is then used to achieve Cu... 2+ and Zn 2+ The long-term controllable sustained release, through polyvinyl alcohol solution and negative pressure conditions for permeation treatment and freeze-thaw cycle cross-linking, allows the tannic acid-repaired loofah fiber skeleton to form a loofah / lithium disilicate glass composite hydrogel with ion-exchange lithium disilicate glass powder.

[0010] The above method, in step one, involves the following process: placing the loofah sponge in a sodium chlorite solution with a pH of 4.8–5.2 and a mass fraction of 0.8%–1.2%, and stirring at 80°C–85°C for 1.9–2.1 hours. In this invention, by controlling the pH and mass fraction of the sodium chlorite solution, a weakly acidic solution is achieved, effectively activating the oxidative activity of sodium chlorite while avoiding excessive acidification of the fiber. By controlling the stirring temperature, a moderate reaction rate is ensured, lignin is fully removed, and thermal degradation of cellulose is prevented. By controlling the stirring time, a balance is achieved between removal efficiency and fiber skeleton retention.

[0011] The surface repair process described in step one of the above method is as follows: The delignified loofah sponge is soaked in a 4.5%–5.5% (w / w) tannic acid aqueous solution for 3 days under oscillation conditions at 34°C–40°C and 90–110 rpm, and then dried at 35°C–45°C. This invention, by controlling the mass fraction and temperature of the tannic acid aqueous solution, facilitates the uniform adsorption and self-assembly of tannic acid molecules on the surface of the loofah sponge. The gentle oscillation at 90–110 rpm promotes mass transfer while avoiding mechanical damage. Controlling the soaking time ensures sufficient surface modification to introduce phenolic hydroxyl active sites. Controlling the drying temperature gently removes moisture, preventing tannic acid oxidation or fiber embrittlement caused by high temperatures.

[0012] The preparation process of lithium disilicate glass in step two of the above method is as follows: Li2CO3 and SiO2 are mixed in a molar ratio of 1:2, then melted once, quenched in water, and melted again, and then poured into a graphite mold preheated to 440°C for shaping, and annealed at 440°C for 30 minutes; the temperature of the first melting is 1450°C~1500°C, and the processes of the first melting and the second melting are the same. This invention decomposes the raw materials and forms a uniform glass melt by melting Li2CO3 and SiO2 once, and rapidly cools the melt into granular glass particles by water quenching to break the ordered structure and promote subsequent uniform remelting. The temperature of the second melting is the same as that of the first melting. The second melting can eliminate the internal stress and compositional inhomogeneity generated by water quenching, resulting in a more homogeneous and stable glass melt. Preheating the graphite mold avoids cracking caused by rapid cooling when the high-temperature glass melt comes into contact with the cold mold, and facilitates forming flow. Annealing effectively releases the thermal stress generated during forming and cooling, enhancing the mechanical integrity of the glass.

[0013] In the above method, the mixed molten salt in step three is prepared by using ZnCl2 and CuCl in a molar ratio of 7:3. The ion exchange treatment is carried out at a temperature of 280℃~330℃ for 12h~96h. In this invention, by controlling the molar ratio of ZnCl2 to CuCl, an appropriate amount of Cu is provided. + Ions and Zn 2+ Ion synergy to achieve Li on glass surface + / Cu + While exchanging ions, excessive crystallization is suppressed. By controlling the temperature of the ion exchange treatment, sufficient ion diffusion rate is ensured while avoiding glass structure relaxation or accelerated salt bath volatilization. The ion exchange treatment time is controlled, allowing for flexible adjustment based on the desired ion exchange depth and optical / mechanical properties; longer treatment times result in thicker exchange layers, and Cu... + The higher the doping concentration.

[0014] In the above method, the mass fraction of the polyvinyl alcohol solution in step four is 7.5%~17.5%, the mass ratio of the added ion-exchange lithium disilicate glass powder to water is 5:100, the stirring temperature is 94.5℃~95.5℃, and the stirring time is 1h~2h. This invention achieves an optimized balance between crosslinking ability and mechanical strength by controlling the mass concentration of the polyvinyl alcohol solution, facilitating the formation of a continuous hydrogel network. By controlling the mass ratio of the added ion-exchange lithium disilicate glass powder to water, it ensures uniform dispersion of the glass powder while avoiding excessive filler leading to increased gel brittleness. By controlling the stirring temperature, high-temperature stirring accelerates the complete dissolution of PVA and reduces solution viscosity, which is beneficial for the dispersion and wetting of the glass powder. By controlling the stirring time, uniform mixing is achieved without causing polyvinyl alcohol degradation.

[0015] In the above method, the negative pressure condition in step five is 0.5MPa~1.5MPa, the penetration treatment time is 10min~20min, and the number of freeze-thaw crosslinking cycles is three. The freeze-thaw crosslinking process is as follows: freezing at -80℃ for 20h, followed by thawing at 4℃ for 4h. This invention effectively removes air bubbles from the composite system and promotes the solution's penetration into the pores of the loofah sponge by controlling the negative pressure condition. By controlling the penetration treatment time, sufficient wetting is achieved without excessive compression of the skeleton. By employing three freeze-thaw crosslinking cycles, stable polyvinyl alcohol microcrystalline crosslinking points are gradually formed. Controlling the cryogenic temperature rapidly induces the formation of a large number of crystal nuclei. After three cycles, the mechanical strength and structural stability of the gel reach their optimal levels. Controlling the freezing time ensures sufficient crystallization, and controlling the thawing temperature and time facilitates molecular chain rearrangement and internal stress release.

[0016] In addition, the present invention provides an application of a loofah / lithium disilicate glass composite hydrogel, characterized in that the loofah / lithium disilicate glass composite hydrogel is used to prepare bone tissue engineering scaffold materials, wound dressings, or tissue repair materials.

[0017] Compared with the prior art, the present invention has the following advantages: 1. This invention is the first to use tannic acid to repair the surface of delignified loofah sponge, and to construct a three-phase synergistic reinforcement system of fiber skeleton-inorganic particles-polymer matrix by combining it with ion-exchange lithium disilicate glass powder and polyvinyl alcohol. The abundant polyphenolic hydroxyl groups in the tannic acid molecule effectively fill and repair the microscopic damage on the fiber surface caused by delignification, and on the other hand, act as molecular bridges to enhance the interfacial bonding between the fiber skeleton and the polyvinyl alcohol matrix. As a result, the mechanical properties of the composite hydrogel are significantly better than those of the comparative material without tannic acid modification or without the addition of bioactive glass. Its compressive strength reaches the level that is compatible with human cancellous bone, and can provide sufficient mechanical support for bone defect repair.

[0018] 2. This invention introduces Zn into lithium disilicate glass simultaneously using a molten salt ion exchange strategy. 2+ and Cu + Furthermore, by leveraging the strong chelating effect of tannic acid and the physical confinement effect of the polyvinyl alcohol network, Cu was achieved. 2+ / Zn 2+ Compared with uncomposite bioactive glass powder, the composite hydrogel of this invention exhibits significantly reduced cumulative ion release over 28 days, with a smooth release curve and no burst release, effectively avoiding the cytotoxicity risk caused by burst ion release.

[0019] 3. This invention endows the composite hydrogel with excellent antioxidant and anti-inflammatory properties by introducing tannic acid. The polyphenolic structure of tannic acid enables the composite hydrogel to have a high efficiency in scavenging free radicals, which can effectively remove reactive oxygen species and alleviate oxidative stress, providing a new strategy for the regulation of the immune microenvironment of infectious bone defects.

[0020] 4. This invention couples the interfacial antibacterial / anti-adhesion effects of tannic acid with the chemical bactericidal effects of Zn / Cu bimetallic ions, and optimizes the release behavior through complexation regulation of the hydrogel network and tannic acid. This achieves both immediate and long-lasting antibacterial effects without relying on antibiotics. After 21 days of pre-soaking, the final extract of the composite hydrogel of this invention maintains a high inhibition rate against both Gram-negative and Gram-positive bacteria, significantly outperforming comparative materials containing only bioactive glass or only tannic acid. This solves the problem of existing single-Zn... 2+ The technical challenge of the system's long-lasting antibacterial ability decaying.

[0021] 5. This invention uses polyvinyl alcohol for physical freeze-thaw crosslinking, avoiding the cytotoxic risks of chemical crosslinking agents or residual monomers; the raw material, loofah sponge, is agricultural waste, and the bioactive glass component has good biocompatibility. The overall preparation process is green, environmentally friendly, and low-cost, and has good prospects for clinical translation.

[0022] 6. The preparation method of the present invention is simple to operate and the process is controllable. By adjusting the ion exchange temperature, time and tannic acid modification conditions, the mechanical properties, ion release rate and degradation behavior of the composite hydrogel can be flexibly controlled to meet the personalized needs of different bone defect repair scenarios.

[0023] 7. This invention uses natural loofah sponge as a three-dimensional fiber skeleton, making full use of its wide availability and renewable characteristics, realizing the high-value utilization of agricultural waste, reducing the preparation cost of bone repair materials, and meeting the requirements of sustainable development.

[0024] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0025] Figure 1 The compressive stress-strain curves of the composite hydrogel prepared in Example 1 of the present invention and the hydrogels prepared in Comparative Examples 1 to 4 are shown.

[0026] Figure 2 The compressive strength of the composite hydrogel prepared in Example 1 of the present invention and the hydrogels prepared in Comparative Examples 1 to 4 at 70% strain is statistically shown.

[0027] Figure 3 The compressive modulus statistics of the composite hydrogel prepared in Example 1 of the present invention and the hydrogels prepared in Comparative Examples 1 to 4 are shown in the figure.

[0028] Figure 4 The cumulative release curves of Cu ions over 28 days for the composite hydrogel prepared in Example 1 of this invention, the hydrogel prepared in Comparative Example 2, and BG powder are shown.

[0029] Figure 5 The cumulative release curves of Zn ions over 28 days are shown for the composite hydrogel prepared in Example 1 of this invention, the hydrogel prepared in Comparative Example 2, and BG powder.

[0030] Figure 6 The UV-Vis absorption spectra of the composite hydrogel prepared in Example 1 of this invention and the hydrogels prepared in Comparative Examples 1 to 3 are shown in the figure.

[0031] Figure 7 The above is a statistical chart showing the DPPH free radical scavenging efficiency of the composite hydrogel prepared in Example 1 of this invention and the hydrogels prepared in Comparative Examples 1 to 3.

[0032] Figure 8 The statistical chart shows the inhibition rate of the composite hydrogel prepared in Example 1 of this invention, the hydrogel prepared in Comparative Examples 1-3, BG, LD and blank control group after 21 days of pre-soaking and 7 days of extraction on Escherichia coli.

[0033] Figure 9 The statistical chart shows the inhibition rate of Staphylococcus aureus on the composite hydrogel prepared in Example 1 of this invention, the hydrogel prepared in Comparative Examples 1-3, BG, LD and blank control group after 21 days of pre-soaking and 7 days of extraction.

[0034] Figure 10 The survival rates of MC3T3-E1 cells treated with 5% extracts of BG and LD for 1, 3, and 5 days were measured for the composite hydrogel prepared in Example 1 of this invention, the hydrogel prepared in Comparative Examples 1 to 3, and BG and LD.

[0035] Figure 11 Quantitative statistical analysis of ALP levels in MC3T3-E1 cells cultured in 5% extracts of the composite hydrogel prepared in Example 1 of this invention and the hydrogels prepared in Comparative Examples 1-3 for 7 and 14 days. Detailed Implementation

[0036] Example 1 This embodiment includes the following steps: Step 1: Soak and wash the natural loofah sponge with deionized water, then dry it in an 80℃ oven. Next, cut it into 20mm×20mm×20mm cubes to obtain loofah sponge blocks. Prepare a 1% sodium chlorite solution and adjust the pH to 5 with glacial acetic acid. Then immerse the loofah sponge blocks in the sodium chlorite solution and stir in an 83℃ water bath for 2 hours. After that, take out the loofah sponge blocks, wash them 5 times with deionized water, and soak them in deionized water for later use to obtain delignified loofah sponge, denoted as WLS. Then take out the WLS and dry it. Soak it in a 5% tannic acid aqueous solution at 37℃ and a shaking speed of 100 rpm for 3 days. Finally, dry it in an oven at 40℃ for 4 hours to obtain a tannic acid-repaired loofah sponge fiber skeleton, denoted as WLS@TA. Step 2: Lithium carbonate and silicon dioxide with a particle size of 2μm are mixed at a molar ratio of 1:2, then placed in a platinum crucible. The mixture is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes, followed by heating to 1500℃ and holding for 10 minutes to achieve a single melting process, yielding molten glass. The molten glass is then rapidly quenched in deionized water at room temperature to obtain glass slag. After drying the glass slag, it is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes. After heating to 1500℃ and holding for 10 minutes, a second melting process is carried out. Then, it is poured into a graphite mold with a diameter × height of 10mm × 60mm that has been preheated at 440℃ to form. After forming, it continues to be annealed at 440℃ for 30 minutes with the graphite mold to eliminate internal stress. Finally, the formed glass rod is cut into round pieces with a diameter × height of 10mm × 1mm using a diamond cutter, and then polished on both sides until the surface is smooth to obtain lithium disilicate glass, denoted as LD. Step 3: Mix 30.503g ZnCl2 and 9.497g CuCl in a molar ratio of 7:3, then place the mixture in an alumina crucible and melt it at 380℃ for 4 hours, stirring once every hour during the process, to obtain a mixed molten salt. Then, vertically insert a piece of lithium disilicate glass obtained in Step 2 into the mixed molten salt to completely embed the lithium disilicate glass. Subsequently, transfer it to a tube furnace and hold it at 330℃ for 24 hours for ion exchange. After the exchange is completed, remove the ion-exchanged lithium disilicate glass, cool it to room temperature in air, then ultrasonically clean it with deionized water, then initially crush it in a stainless steel mortar, and then grind it in a planetary ball mill for 24 hours to obtain ion-exchanged lithium disilicate glass powder, denoted as BG. Step 4: Mix polyvinyl alcohol with ultrapure water and heat and stir at 95°C until completely dissolved to form a transparent and uniform polyvinyl alcohol solution with a mass fraction of 12.5%. Then add the BG obtained in Step 3 at a mass ratio of BG to ultrapure water of 5:100 and continue stirring at 95°C for 1.5 hours to obtain the precursor solution, denoted as BG-PVA. Step 5: Immerse the WLS@TA obtained in Step 1 into a mold containing the BG-PVA obtained in Step 4, making the mass ratio of WLS@TA to BG-PVA 0.05:1 (mass in g, volume in mL). Then place it in a vacuum desiccator and perform infiltration treatment under a negative pressure of 1 MPa for 15 min. Finally, perform three freeze-thaw cycles for crosslinking. Each freeze-thaw cycle involves freezing at -80℃ for 20 h, followed by thawing at 4℃ for 4 h, to obtain the loofah / lithium disilicate glass composite hydrogel, denoted as WLS@TA / BG-PVA composite hydrogel.

[0037] Comparative Example 1 The difference between this comparative example and Example 1 is that the surface repair by immersion in tannic acid solution in step one is omitted, WLS obtained in step one is used instead of WLS@TA in step five, and BG powder is not added in step four. The resulting hydrogel is denoted as WLS / PVA hydrogel.

[0038] Comparative Example 2 The difference between this comparative example and Example 1 is that the surface repair by immersion in tannic acid solution in step one is omitted, and the WLS obtained in step one is used instead of WLS@TA in step five. The resulting hydrogel is denoted as WLS / BG-PVA hydrogel.

[0039] Comparative Example 3 The difference between this comparative example and Example 1 is that BG powder is not added in step four, and the resulting hydrogel is denoted as WLS@TA / PVA hydrogel.

[0040] Comparative Example 4 The difference between this comparative example and Example 1 is that steps one, two and three are omitted, BG powder is not added in step four, and the resulting hydrogel is denoted as PVA hydrogel.

[0041] The performance of the hydrogels prepared in Example 1 and Comparative Examples 1-4 was tested and evaluated below.

[0042] (a) Mechanical compressive performance test The hydrogels prepared in Example 1 and Comparative Examples 1-4, with dimensions of 15mm × 15mm × 8mm, were subjected to compression tests using a universal testing machine. The compression speed was 2mm / min, and the maximum strain was fixed at 70%. The compressive modulus was calculated from the slope of the compressive stress-strain curve within the strain range of 5% to 15%. All tests for each hydrogel were repeated at least three times to ensure statistical reliability. The test results are as follows: Figures 1-3As shown, PVA is Comparative Example 4, WLS / PVA is Comparative Example 1, WLS / BG-PVA is Comparative Example 2, WLS@TA / PVA is Comparative Example 3, and WLS@TA / BG-PVA is Example 1.

[0043] from Figures 1-3 As can be seen, the compressive strength of the PVA hydrogel in Comparative Example 4 was only 0.444 MPa, and the compressive modulus was 0.0416 MPa; the compressive strength of the WLS / PVA hydrogel in Comparative Example 1 was increased to 3.981 MPa, and the compressive modulus was 0.601 MPa; the compressive strength of the WLS@TA / PVA hydrogel in Comparative Example 3 was further increased to 5.870 MPa, and the compressive modulus was 0.885 MPa; the compressive strength of the WLS / BG-PVA hydrogel in Comparative Example 2 was 5.584 MPa, and the compressive modulus was 0.626 MPa; while the WLS@TA / BG-PVA composite hydrogel in Example 1 exhibited the best mechanical properties, with a compressive strength of 8.631 MPa and a compressive modulus of 1.226 MPa, which was about 20 times higher than that of the PVA hydrogel in Comparative Example 4, and the difference between the groups was statistically significant.

[0044] The above results indicate that TA surface repair and BG particle reinforcement have a synergistic effect. As a molecular bridge, TA's abundant phenolic hydroxyl groups can form multiple hydrogen bonds with the cellulose hydroxyl groups on the WLS fiber surface and the hydroxyl groups on the PVA molecular chain, significantly enhancing the interfacial bonding strength between the fiber skeleton and the PVA matrix. At the same time, TA effectively fills and repairs the submicron-level corrosion pores on the fiber surface caused by delignification, restoring the structural continuity of the fiber skeleton. In addition, BG particles, as an inorganic reinforcing phase, are uniformly dispersed in the PVA matrix, playing a role in stress transfer and load distribution. The three synergistic effects achieve a significant improvement in mechanical properties.

[0045] (ii) Ion release performance test In Example 1 and Comparative Example 2, the hydrogels and BG powders were soaked in Tris-HCl solution (pH=7.4) at a solid-liquid ratio of 0.1 g / mL and cultured in a constant temperature incubator at 37℃. Extracts were collected at predetermined time points (0.5, 1, 3, 5, 7, 14, 21, and 28 days). The concentrations of Cu and Zn ions were determined using inductively coupled plasma optical emission spectrometry (ICP-OES), and the cumulative release was calculated. The test results are as follows: Figure 4 and Figure 5 As shown, BG is BG powder, WLS / BG-PVA is Comparative Example 2, and WLS@TA / BG-PVA is Example 1. Figure 4 The small images in the diagram are enlarged views of Comparative Example 2 and Example 1. Figure 5 The small images in the diagram are enlarged views of Comparative Example 2 and Example 1.

[0046] from Figure 4 and Figure 5 It can be seen that BG powder exhibits a violent burst release, with a cumulative release of Cu ions of 611.5±9.8 mg / L and Zn ions of 47.7±1.4 mg / L after 28 days. In contrast, in the WLS / BG-PVA hydrogel of Comparative Example 2, the cumulative release of Cu ions after 28 days decreased to 25.6±1.2 mg / L and Zn ions to 2.4±0.2 mg / L. In the WLS@TA / BG-PVA composite hydrogel of Example 1, the cumulative release of Cu ions after 28 days was only 2.6±0.3 mg / L and Zn ions was 2.1±0.1 mg / L, which is more than two orders of magnitude lower than that of BG powder, and the release curve is flat without sudden release.

[0047] The above results indicate that the strong chelating effect of TA and the physical confinement of the PVA network synergistically regulate the ion release behavior, and the abundant pyrogallol structure in the TA molecule has a significant effect on Cu. 2+ and Zn 2+ The high-affinity chelating sites can form a dynamic metal-polyphenol complex layer on the surface of BG particles through coordination. This complex layer inhibits the rapid dissolution of free ions on the BG surface through a physical barrier effect, and achieves gradient slow release of ions through a dynamic balance of complexation and dissociation. That is, the metal ions complexed on the surface slowly dissociate and are released in the body fluid environment, while the ions inside need to overcome the blockage of the complex layer before diffusing outward, thereby inhibiting the burst release of free ions on the BG surface from the root. Therefore, the composite hydrogel system of the present invention essentially constructs a multi-level controlled-release structure of BG interior, surface complex layer, and polymer network, realizing a dynamic balance between chelation reservoir and gradient slow release, overcoming the cytotoxicity problem caused by burst release of ions in the prior art, and keeping the release concentration controlled between the physiological safety threshold and the functional effective window throughout the process.

[0048] (III) Antioxidant performance test The in vitro antioxidant capacity of the materials was evaluated using a DPPH free radical scavenging assay. The hydrogels prepared in Example 1 and Comparative Examples 1-3 were shredded and added to PBS solution at a solid-liquid ratio of 0.2 g / mL. The mixtures were shaken at 37°C and 100 rpm for 30 min. The supernatant was used as the sample extraction solution. A 0.05 mmol / L DPPH anhydrous ethanol solution was prepared. The reaction system was set up as follows: Sample group (As) consisted of 3 mL of DPPH working solution mixed with 200 μL of sample extraction solution; Blank control group (Ac) consisted of 3 mL of anhydrous ethanol mixed with 200 μL of sample extraction solution; Blank group (Ab) consisted of 3 mL of DPPH working solution mixed with 200 μL of PBS. After reacting in the dark for 30 min, the absorption spectrum in the wavelength range of 350–800 nm was scanned using a UV-Vis spectrophotometer, and 517 μL of the spectrum was recorded. The absorbance value at nm, and the DPPH free radical scavenging rate are calculated using the following formula: Scavenging rate (%) = (1 - (As - Ac) / Ab) × 100%, as shown in the test results. Figure 6 and Figure 7 As shown, DPPH is the blank group, WLS / PVA is comparative example 1, WLS / BG-PVA is comparative example 2, WLS@TA / PVA is comparative example 3, and WLS@TA / BG-PVA is example 1.

[0049] from Figure 6 and Figure 7 It can be seen that the WLS / PVA hydrogel of Comparative Example 1 has almost no antioxidant activity, with a DPPH scavenging rate of less than 5%; the WLS / BG-PVA hydrogel of Comparative Example 2 also has a scavenging rate of less than 5%; the WLS@TA / PVA hydrogel of Comparative Example 3 has a DPPH scavenging rate as high as about 91%; the WLS@TA / BG-PVA composite hydrogel of Example 1 has a scavenging rate of about 70%, and still shows good antioxidant activity. The spectrum of the WLS@TA / BG-PVA composite hydrogel of Example 1 shows an additional absorption peak at 420 nm, which is related to the complex formed by polyphenols in TA and Cu / Zn metal ions in BG.

[0050] The above results indicate that the polyphenolic structure of TA is the core source of the material's antioxidant function. The abundant phenolic hydroxyl groups in the TA molecule can act as hydrogen donors, undergoing electron transfer reactions with DPPH free radicals to reduce them to stable hydrazine compounds, thereby quenching free radicals. After being combined with BG, although some phenolic hydroxyl sites complex with metal ions, resulting in a slight decrease in the scavenging rate, the overall free radical scavenging capacity can still be maintained at a high level. This antioxidant property endows the material with the ability to remove local excess reactive oxygen species (ROS) in the early stages of implantation, which helps to alleviate the damage of oxidative stress to surrounding tissues.

[0051] (iv) Antibacterial performance test With Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus The strain was selected as the model strain. The antibacterial properties were evaluated using the co-culture method with extracts. Hydrogels prepared in Example 1, Comparative Examples 1-3, BG, LD, and the blank control group were immersed in sterile PBS at a solid-liquid ratio of 0.1 g / mL for one day at 37°C. The extracts were collected, and the reactivated bacterial culture (OD) was... 600 ≈0.6) was mixed with the extract at a 1:1 volume ratio and co-cultured at 37℃ for 4 h. The co-cultured bacterial solution was serially diluted, and 20 μL was spread on the surface of LB solid medium and incubated overnight at 37℃. Colony forming units (CFU) were counted to calculate the antibacterial rate. To further evaluate the long-term antibacterial performance, each group of samples was pre-soaked in PBS for 21 days to simulate the early release process. After removal, the samples were gently washed with sterile PBS and then transferred to fresh PBS for another 7 days of soaking. The extract during this stage was collected and antibacterial tests were performed according to the above method. The test results are as follows. Figure 8 and Figure 9 As shown, Control is the blank control group, LD is lithium disilicate glass, BG is ion-exchanged lithium disilicate glass, WLS / PVA is comparative example 1, WLS / BG-PVA is comparative example 2, WLS@TA / PVA is comparative example 3, and WLS@TA / BG-PVA is example 1.

[0052] from Figure 8 and Figure 9 It can be seen that the WLS / PVA hydrogel of Comparative Example 1 has almost no antibacterial ability; the antibacterial activity of the WLS / BG-PVA hydrogel of Comparative Example 2 is significantly reduced, with antibacterial rates of only 37.3% (Escherichia coli) and 30.0% (Staphylococcus aureus); the WLS@TA / PVA hydrogel of Comparative Example 3 can still maintain a high level of long-term antibacterial effect; after 21 days of pre-soaking, the WLS@TA / BG-PVA composite hydrogel of Example 1 has an inhibition rate of more than 95% against Escherichia coli and more than 95% against Staphylococcus aureus in the final 7 days of extraction, with an antibacterial rate decrease of less than 4%.

[0053] The above results demonstrate that this invention achieves a synergistic effect of immediate sterilization and long-term antibacterial action. At the mechanistic level, the interfacial antibacterial / anti-adhesion effect of TA is coupled with the chemical bactericidal effect of Zn / Cu bimetallic ions: TA molecules first undergo hydrogen bonding with lipopolysaccharides or teichoic acid on the bacterial cell membrane surface through their polyphenolic hydroxyl groups, weakening the bacterial membrane barrier and adhesion ability, making it easier for metal ions to cross the membrane and enter the bacterial cell to exert a killing effect; simultaneously, the complexation-dissociation dynamic balance between TA and metal ions effectively prevents the rapid depletion of ions through burst release, preserving a sufficient ion reservoir for subsequent long-term antibacterial action. These three elements form a cascade antibacterial mechanism of interfacial weakening-transmembrane killing-continuous replenishment, thus achieving both immediate and long-term antibacterial performance without relying on antibiotics, solving the problem of existing single Zn... 2+ The technical challenge of the system's long-lasting antibacterial ability decaying.

[0054] (v) In vitro biocompatibility and osteogenic performance testing The in vitro biocompatibility of the samples was evaluated using mouse osteoblast MC3T3-E1 cells. The composite hydrogel prepared in Example 1, the hydrogels prepared in Comparative Examples 1-3, BG powder, and LD were soaked in α-MEM complete medium at a solid-liquid ratio of 0.1 g / mL at 37°C for 3 days to prepare an extract. MC3T3-E1 cells were then incubated at a concentration of 1×10⁻⁶ cells / mL. 4 cell / cm 2 Cells were seeded at a density of 5% in 48-well plates and incubated at 37°C in a 5% CO2 incubator for 1, 3, and 5 days. Cell viability was assessed using a CCK-8 assay kit. Live / dead cell staining was performed using a Calcein-AM / PI double staining kit and observed under an inverted fluorescence microscope. Osteogenic differentiation was evaluated using osteogenic induction medium (complete medium supplemented with 1 mM dexamethasone, 10 mM ascorbic acid, and 1 M β-glycerophosphate). MC3T3-E1 cells were co-cultured with 5% infusion medium in osteogenic induction medium for 7 and 14 days. Alkaline phosphatase (ALP) was qualitatively and quantitatively detected using the BCIP / NBT staining method.

[0055] Biocompatibility test results as follows Figure 10 As shown, LD is lithium disilicate glass, BG is ion-exchanged lithium disilicate glass, WLS / PVA is Comparative Example 1, WLS / BG-PVA is Comparative Example 2, WLS@TA / PVA is Comparative Example 3, and WLS@TA / BG-PVA is Example 1. Figure 10It can be seen that, at a 5% extract concentration, the materials in each group showed significant differences in their ability to support the viability of MC3T3-E1 cells. First, the cell viability of BG powder and LD powder was significantly lower than that of other groups at all time points, which is consistent with their violent burst release behavior in the ion release test: high concentrations of Cu and Zn ions rapidly dissolved in a short period of time, exceeding the cell tolerance threshold, triggering oxidative stress and mitochondrial damage, thus leading to a decrease in cell viability. Although the LD group did not undergo ion exchange and did not contain Cu / Zn ions, the unsaturated dissolution of its glass network in the culture medium may release high concentrations of Si and Li ions, which also had a certain toxic effect on the cells. In contrast, Comparative Examples 1-3 and Example 1 all showed significantly better cell compatibility than the pure glass group. This is due to the physical encapsulation and confinement of BG particles by the PVA hydrogel network, which effectively inhibited the burst release of ions.

[0056] Osteogenic differentiation evaluation test results as follows Figure 11 As shown, Control is the blank control group, WLS / PVA is Comparative Example 1, WLS / BG-PVA is Comparative Example 2, WLS@TA / PVA is Comparative Example 3, and WLS@TA / BG-PVA is Example 1. Figure 11 It can be seen that after 7 days of culture, the ALP activity of the Control group and the WLS / PVA hydrogel in Comparative Example 1 was extremely low, with no significant difference between the two, indicating that PVA hydrogel and WLS fibers alone do not possess osteogenic induction activity. The ALP activity of the WLS@TA / PVA hydrogel in Comparative Example 3 was slightly higher than that of the Control group, but still at a low level, indicating that although TA itself has biological functions such as antioxidation, it cannot directly activate the osteogenic differentiation signaling pathway. The ALP activity of the WLS / BG-PVA hydrogel in Comparative Example 2 was significantly increased, reaching about 2.5 times that of the Control group, indicating that the Cu and Zn ions released by the ion-exchange BG are the core driving force for activating osteogenic differentiation, among which Zn 2+ It has been widely reported that activating the MAPK / ERK signaling pathway and the Wnt / β-catenin pathway can promote the expression of osteogenic-related genes; Cu 2+This can indirectly support osteogenic differentiation by stabilizing HIF-1α and promoting the secretion of angiogenesis-related factors. In Example 1, the WLS@TA / BG-PVA composite hydrogel showed the highest ALP activity, approximately three times that of the Control group and significantly higher than Comparative Example 2. After 14 days of culture, ALP activity in all groups increased compared to 7 days, but the trend of difference between groups remained consistent; the Control group and Comparative Example 1 remained at extremely low levels. Comparative Example 3 showed a slight increase, but it was still limited. Comparative Example 2 showed a significant increase in ALP activity. Example 1 maintained the highest level, further widening the gap with Comparative Example 2. This result indicates that although Cu / Zn ions released by BG are the main driving force for activating osteogenic differentiation, TA... The presence of TA further enhances this effect; TA's promoting effect does not directly activate osteogenic signaling pathways, but rather clears reactive oxygen species (ROS) generated during cell metabolism through its polyphenolic structure, reducing oxidative stress levels and thus providing a more optimized cellular microenvironment for osteogenic differentiation; at the same time, the reversible complexation between TA and metal ions maintains the ion concentration in the extract at a relatively stable level, avoiding interference with cell signaling caused by fluctuations in ion concentration; therefore, there is an "indirect escort" synergistic effect between TA and BG: TA does not directly drive osteogenic differentiation, but through microenvironment optimization and ion homeostasis regulation, it enables the osteogenic active ions released by BG to exert their biological functions more persistently and stably.

[0057] The above results indicate that the WLS@TA / BG-PVA composite hydrogel extract of Example 1 can achieve efficient osteogenic initiation through a synergistic mechanism of TA action and ion-driven processes: on the one hand, Zn / Cu ions released by BG act as direct signaling molecules to activate osteogenic differentiation pathways; on the other hand, TA provides a stable, low-oxidation microenvironment for osteogenic differentiation by scavenging ROS and regulating ion release behavior. The synergistic effect of these two processes results in superior osteogenic properties compared to the single BG system, demonstrating that the composite hydrogel of this invention has outstanding in vitro osteogenic potential and can be applied to the preparation of bone tissue engineering scaffold materials, wound dressings, or tissue repair materials.

[0058] Example 2 This embodiment includes the following steps: Step 1: Soak and wash the natural loofah sponge in deionized water, then dry it in an 80℃ oven. Next, cut it into 20mm×20mm×20mm cubes to obtain loofah sponge blocks. Prepare a 0.8% sodium chlorite solution and adjust the pH to 4.8 with glacial acetic acid. Then immerse the loofah sponge blocks in the sodium chlorite solution and stir in an 80℃ water bath for 2.1 hours. After that, take out the loofah sponge blocks, wash them 6 times with deionized water, and soak them in deionized water for later use to obtain delignified loofah sponge, denoted as WLS. Then take out the WLS and dry it. Soak it in a 5.5% tannic acid aqueous solution at 34℃ and a rotation speed of 90 rpm for 3 days. Finally, dry it in an oven at 45℃ for 4 hours to obtain a tannic acid-repaired loofah sponge fiber skeleton, denoted as WLS@TA. Step 2: Lithium carbonate and silicon dioxide with a particle size of 2μm are mixed at a molar ratio of 1:2, then placed in a platinum crucible. The mixture is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes, followed by heating to 1500℃ and holding for 10 minutes to achieve a single melting process, yielding molten glass. The molten glass is then rapidly quenched in deionized water at room temperature to obtain glass slag. After drying the glass slag, it is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes. After heating to 1500℃ and holding for 10 minutes, a second melting process is carried out. Then, it is poured into a graphite mold with a diameter × height of 10mm × 60mm that has been preheated at 440℃ to form. After forming, it continues to be annealed at 440℃ for 30 minutes with the graphite mold to eliminate internal stress. Finally, the formed glass rod is cut into round pieces with a diameter × height of 10mm × 1mm using a diamond cutter, and then polished on both sides until the surface is smooth to obtain lithium disilicate glass, denoted as LD. Step 3: Mix 30.503g ZnCl2 and 9.497g CuCl in a molar ratio of 7:3, then place the mixture in an alumina crucible and melt it at 380℃ for 4 hours, stirring once every hour during the process, to obtain a mixed molten salt. Then, vertically insert a piece of lithium disilicate glass obtained in Step 2 into the mixed molten salt to completely embed the lithium disilicate glass. Subsequently, transfer it to a tube furnace and hold it at 280℃ for 48 hours for ion exchange. After the exchange is completed, remove the ion-exchanged lithium disilicate glass, cool it to room temperature in air, then ultrasonically clean it with deionized water, then initially crush it in a stainless steel mortar, and then grind it in a planetary ball mill for 24 hours to obtain ion-exchanged lithium disilicate glass powder, denoted as BG. Step 4: Mix polyvinyl alcohol with ultrapure water and heat and stir at 94.5℃ until completely dissolved to form a transparent and uniform polyvinyl alcohol solution with a mass fraction of 17.5%. Then add the BG obtained in Step 3 at a mass ratio of BG to ultrapure water of 5:100 and continue stirring at 94.5℃ for 2 hours to obtain the precursor solution, denoted as BG-PVA. Step 5: Immerse the WLS@TA obtained in Step 1 into a mold containing the BG-PVA obtained in Step 4, ensuring that the mass ratio of WLS@TA to BG-PVA is 0.05:1 (mass in g, volume in mL). Then place it in a vacuum desiccator and perform a permeation treatment under a negative pressure of 0.5 MPa for 20 min. Finally, perform three freeze-thaw cycles for crosslinking. Each freeze-thaw cycle involves freezing at -80℃ for 20 h, followed by thawing at 4℃ for 4 h, to obtain a loofah / lithium disilicate glass composite hydrogel, denoted as WLS@TA / BG-PVA.

[0059] Example 3 This embodiment includes the following steps: Step 1: Soak and wash the natural loofah sponge in deionized water, then dry it in an 80℃ oven. Next, cut it into 20mm×20mm×20mm cubes to obtain loofah sponge blocks. Prepare a 1.2% sodium chlorite solution and adjust the pH to 5.2 with glacial acetic acid. Then immerse the loofah sponge blocks in the sodium chlorite solution and stir in an 85℃ water bath for 1.9 hours. After that, take out the loofah sponge blocks, wash them 5 times with deionized water, and soak them in deionized water for later use to obtain delignified loofah sponge, denoted as WLS. Then take out the WLS and dry it. Soak it in a 4.5% tannic acid aqueous solution at 40℃ and a rotation speed of 110 rpm for 3 days. Finally, dry it in an oven at 35℃ for 4 hours to obtain a tannic acid-repaired loofah sponge fiber skeleton, denoted as WLS@TA. Step 2: Lithium carbonate and silicon dioxide with a particle size of 2μm are mixed at a molar ratio of 1:2, then placed in a platinum crucible. The mixture is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes, followed by heating to 1500℃ and holding for 10 minutes to achieve a single melting process, yielding molten glass. The molten glass is then rapidly quenched in deionized water at room temperature to obtain glass slag. After drying the glass slag, it is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes. After heating to 1500℃ and holding for 10 minutes, a second melting process is carried out. Then, it is poured into a graphite mold with a diameter × height of 10mm × 60mm that has been preheated at 440℃ to form. After forming, it continues to be annealed at 440℃ for 30 minutes with the graphite mold to eliminate internal stress. Finally, the formed glass rod is cut into round pieces with a diameter × height of 10mm × 1mm using a diamond cutter, and then polished on both sides until the surface is smooth to obtain lithium disilicate glass, denoted as LD. Step 3: Mix 30.503g ZnCl2 and 9.497g CuCl in a molar ratio of 7:3, then place the mixture in an alumina crucible and melt it at 380℃ for 4 hours, stirring once every hour during the process, to obtain a mixed molten salt. Then, vertically insert a piece of lithium disilicate glass obtained in Step 2 into the mixed molten salt to completely embed the lithium disilicate glass. Subsequently, transfer it to a tube furnace and hold it at 280℃ for 96 hours for ion exchange. After the exchange is completed, remove the ion-exchanged lithium disilicate glass, cool it to room temperature in air, then ultrasonically clean it with deionized water, then initially crush it in a stainless steel mortar, and then grind it in a planetary ball mill for 24 hours to obtain ion-exchanged lithium disilicate glass powder, denoted as BG. Step 4: Mix polyvinyl alcohol with ultrapure water and heat and stir at 95.5°C until completely dissolved to form a transparent and uniform polyvinyl alcohol solution with a mass fraction of 7.5%. Then, add the BG obtained in Step 3 at a mass ratio of BG to ultrapure water of 5:100 and continue stirring at 95.5°C for 1 hour to obtain the precursor solution, denoted as BG-PVA. Step 5: Immerse the WLS@TA obtained in Step 1 into a mold containing the BG-PVA obtained in Step 4, making the mass ratio of WLS@TA to BG-PVA 0.05:1 (mass in g, volume in mL). Then place it in a vacuum desiccator and perform infiltration treatment under a negative pressure of 1.5 MPa for 10 min. Finally, perform three freeze-thaw cycles for crosslinking. Each freeze-thaw cycle involves freezing at -80℃ for 20 h, followed by thawing at 4℃ for 4 h, to obtain a loofah / lithium disilicate glass composite hydrogel, denoted as WLS@TA / BG-PVA.

[0060] Example 4 This embodiment includes the following steps: Step 1: Soak and wash the natural loofah sponge in deionized water, then dry it in an 80℃ oven. Next, cut it into 20mm×20mm×20mm cubes to obtain loofah sponge blocks. Prepare a 1.1% sodium chlorite solution and adjust the pH to 5 with glacial acetic acid. Then immerse the loofah sponge blocks in the sodium chlorite solution and stir in an 83℃ water bath for 2 hours. After that, take out the loofah sponge blocks, wash them 6 times with deionized water, and soak them in deionized water for later use to obtain delignified loofah sponge, denoted as WLS. Then take out the WLS and dry it. Soak it in a 5.2% tannic acid aqueous solution at 37℃ and a shaking speed of 100 rpm for 3 days. Finally, dry it in an oven at 40℃ for 4 hours to obtain a tannic acid-repaired loofah sponge fiber skeleton, denoted as WLS@TA. Step 2: Lithium carbonate and silicon dioxide with a particle size of 2μm are mixed at a molar ratio of 1:2, then placed in a platinum crucible. The mixture is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes, followed by heating to 1500℃ and holding for 10 minutes to achieve a single melting process, yielding molten glass. The molten glass is then rapidly quenched in deionized water at room temperature to obtain glass slag. After drying the glass slag, it is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes. After heating to 1500℃ and holding for 10 minutes, a second melting process is carried out. Then, it is poured into a graphite mold with a diameter × height of 10mm × 60mm that has been preheated at 440℃ to form. After forming, it continues to be annealed at 440℃ for 30 minutes with the graphite mold to eliminate internal stress. Finally, the formed glass rod is cut into round pieces with a diameter × height of 10mm × 1mm using a diamond cutter, and then polished on both sides until the surface is smooth to obtain lithium disilicate glass, denoted as LD. Step 3: Mix 30.503g ZnCl2 and 9.497g CuCl in a molar ratio of 7:3, then place the mixture in an alumina crucible and melt it at 380℃ for 4 hours, stirring once every 1 hour to obtain a mixed molten salt. Then, vertically insert a piece of lithium disilicate glass obtained in Step 2 into the mixed molten salt to completely embed the lithium disilicate glass. Subsequently, transfer it to a tube furnace and hold it at 330℃ for 12 hours for ion exchange. After the exchange is completed, remove the ion-exchanged lithium disilicate glass, cool it to room temperature in air, then ultrasonically clean it with deionized water, then initially crush it in a stainless steel mortar, and then grind it in a planetary ball mill for 24 hours to obtain ion-exchanged lithium disilicate glass powder, denoted as BG. Step 4: Mix polyvinyl alcohol with ultrapure water and heat and stir at 95°C until completely dissolved to form a transparent and uniform polyvinyl alcohol solution with a mass fraction of 10%. Then add the BG obtained in Step 3 at a mass ratio of BG to ultrapure water of 5:100 and continue stirring at 95°C for 1.5 hours to obtain the precursor solution, denoted as BG-PVA. Step 5: Immerse the WLS@TA obtained in Step 1 into a mold containing the BG-PVA obtained in Step 4, making the mass ratio of WLS@TA to BG-PVA 0.05:1 (mass in g, volume in mL). Then place it in a vacuum desiccator and perform infiltration treatment under a negative pressure of 1 MPa for 15 min. Finally, perform three freeze-thaw cycles for crosslinking. Each freeze-thaw cycle involves freezing at -80℃ for 20 h and then thawing at 4℃ for 4 h to obtain a loofah / lithium disilicate glass composite hydrogel, denoted as WLS@TA / BG-PVA.

[0061] Example 5 This embodiment includes the following steps: Step 1: Soak and wash natural loofah sponge with deionized water, then dry it in an 80℃ oven. Next, cut it into 20mm×20mm×20mm cubes to obtain loofah sponge blocks. Prepare a 1% sodium chlorite solution and adjust the pH to 5 with glacial acetic acid. Then immerse the loofah sponge blocks in the sodium chlorite solution and stir in a water bath at 80℃~85℃ for 2 hours. After that, take out the loofah sponge blocks, wash them 5~6 times with deionized water, and soak them in deionized water for later use to obtain delignified loofah sponge, denoted as WLS. Then take out the WLS and dry it, then soak it in a 5% tannic acid aqueous solution at 37℃ and a shaking speed of 100rpm for 3 days. Finally, dry it in an oven at 40℃ for 4 hours to obtain a tannic acid-repaired loofah sponge fiber skeleton, denoted as WLS@TA. Step 2: Lithium carbonate and silicon dioxide with a particle size of 2μm are mixed at a molar ratio of 1:2, then placed in a platinum crucible. The mixture is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes, followed by heating to 1500℃ and holding for 10 minutes to achieve a single melting process, yielding molten glass. The molten glass is then rapidly quenched in deionized water at room temperature to obtain glass slag. After drying the glass slag, it is heated to 1450℃ in a high-temperature resistance furnace and held for 60 minutes. After heating to 1500℃ and holding for 10 minutes, a second melting process is carried out. Then, it is poured into a graphite mold with a diameter × height of 10mm × 60mm that has been preheated at 440℃ to form. After forming, it continues to be annealed at 440℃ for 30 minutes with the graphite mold to eliminate internal stress. Finally, the formed glass rod is cut into round pieces with a diameter × height of 10mm × 1mm using a diamond cutter, and then polished on both sides until the surface is smooth to obtain lithium disilicate glass, denoted as LD. Step 3: Mix 30.503g ZnCl2 and 9.497g CuCl in a molar ratio of 7:3, then place the mixture in an alumina crucible and melt it at 380℃ for 4 hours, stirring once every 1 hour to obtain a mixed molten salt. Then, vertically insert a piece of lithium disilicate glass obtained in Step 2 into the mixed molten salt to completely embed the lithium disilicate glass. Subsequently, transfer it to a tube furnace and hold it at 300℃ for 36 hours for ion exchange. After the exchange is completed, remove the ion-exchanged lithium disilicate glass, cool it to room temperature in air, then ultrasonically clean it with deionized water, then initially crush it in a stainless steel mortar, and then grind it in a planetary ball mill for 24 hours to obtain ion-exchanged lithium disilicate glass powder, denoted as BG. Step 4: Mix polyvinyl alcohol with ultrapure water and heat and stir at 95°C until completely dissolved to form a transparent and uniform polyvinyl alcohol solution with a mass fraction of 12.5%. Then add the BG obtained in Step 3 at a mass ratio of BG to ultrapure water of 5:100 and continue stirring at 95°C for 1.5 hours to obtain the precursor solution, denoted as BG-PVA. Step 5: Immerse the WLS@TA obtained in Step 1 into a mold containing the BG-PVA obtained in Step 4, making the mass ratio of WLS@TA to BG-PVA 0.05:1 (mass in g, volume in mL). Then place it in a vacuum desiccator and perform infiltration treatment under a negative pressure of 1 MPa for 15 min. Finally, perform three freeze-thaw cycles for crosslinking. Each freeze-thaw cycle involves freezing at -80℃ for 20 h and then thawing at 4℃ for 4 h to obtain a loofah / lithium disilicate glass composite hydrogel, denoted as WLS@TA / BG-PVA.

[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.

Claims

1. A loofah sponge / lithium disilicate glass composite hydrogel, characterized in that, The composite hydrogel comprises a loofah fiber skeleton that has been surface-repaired with delignified lignin and tannic acid, and a composite hydrogel matrix that fills and coats the loofah fiber skeleton; the composite hydrogel matrix is ​​composed of polyvinyl alcohol and ion-exchange lithium disilicate glass powder.

2. A method for preparing the loofah / lithium disilicate glass composite hydrogel as described in claim 1, characterized in that, The method includes the following steps: Step 1: The loofah sponge is subjected to delignification treatment to obtain delignified loofah sponge. Then, the delignified loofah sponge is soaked in tannic acid solution for surface repair to obtain tannic acid surface-repaired loofah sponge fiber skeleton. Step 2: Prepare lithium disilicate glass using lithium carbonate and silicon dioxide as raw materials; Step 3: Place the lithium disilicate glass prepared in Step 2 in a container containing Zn. 2+ and Cu + The mixture of molten salts is subjected to ion exchange treatment, followed by crushing and grinding to obtain ion-exchanged lithium disilicate glass powder; Step 4: Mix polyvinyl alcohol with water and heat to dissolve, forming a polyvinyl alcohol solution. Then add the ion-exchange lithium disilicate glass powder obtained in Step 3 and stir evenly to obtain a precursor solution. Step 5: Immerse the tannic acid-repaired loofah fiber skeleton obtained in Step 1 into the precursor solution obtained in Step 4, perform infiltration treatment under negative pressure, and then perform at least one freeze-thaw cycle crosslinking to obtain a loofah / lithium disilicate glass composite hydrogel.

3. The method according to claim 2, characterized in that, The process of delignification treatment described in step one is as follows: place the loofah sponge in a sodium chlorite solution with a pH of 4.8~5.2 and a mass fraction of 0.8%~1.2%, and stir at 80℃~85℃ for 1.9h~2.1h.

4. The method according to claim 2, characterized in that, The surface repair process described in step one is as follows: the delignified loofah sponge is soaked in a tannic acid aqueous solution with a mass fraction of 4.5%~5.5% for 3 days under the condition of oscillation at 34℃~40℃ and a rotation speed of 90rpm~110rpm, and then dried at 35℃~45℃.

5. The method according to claim 2, characterized in that, The preparation process of lithium disilicate glass in step two is as follows: Li2CO3 and SiO2 are mixed in a molar ratio of 1:2, and then after one melting, water quenching and a second melting, the mixture is poured into a graphite mold preheated to 440°C and annealed at 440°C for 30 minutes; the temperature of the first melting is 1450°C to 1500°C, and the first melting and second melting processes are the same.

6. The method according to claim 2, characterized in that, The mixed molten salt in step three is prepared by ZnCl2 and CuCl in a molar ratio of 7:

3. The ion exchange treatment is carried out at a temperature of 280℃~330℃ for a time of 12h~96h.

7. The method according to claim 2, characterized in that, In step four, the polyvinyl alcohol solution has a mass fraction of 7.5% to 17.5%, the mass ratio of the added ion-exchange lithium disilicate glass powder to water is 5:100, the stirring temperature is 94.5℃ to 95.5℃, and the stirring time is 1h to 2h.

8. The method according to claim 2, characterized in that, The negative pressure condition in step five is 0.5MPa~1.5MPa, and the permeation treatment time is 10min~20min; the number of freeze-thaw cycle crosslinking is three times, and the freeze-thaw cycle crosslinking process is as follows: freezing at -80℃ for 20h, followed by thawing at 4℃ for 4h.

9. An application of the loofah / lithium disilicate glass composite hydrogel as described in claim 1, characterized in that, The loofah / lithium disilicate glass composite hydrogel is used to prepare bone tissue engineering scaffold materials, wound dressings, or tissue repair materials.

Citation Information

Patent Citations

  • Delignification loofah sponge, loofah sponge based hydrogel and preparation method of delignification loofah sponge based hydrogel

    CN118599141A